(untitled) (Revista de Educação Pública, 2012)
Este artigo tem como objetivo analisar os sentidos relacionados ao conceito de interdisciplinaridade nos Parâmetros Curriculares Nacionais (PCNs) de Ensino Fundamental e Ensino Médio. Utilizamos um método de análise conceitual, proposto por Coombs e Daniels, que possibilita investigar um conceito em um conjunto de textos. A análise apontou diferentes significados associados à interdisciplinaridade: abordagem epistemológica, modo de articular conteúdos, forma de contribuição das disciplinas, forma de organizar as disciplinas em projetos, perspectiva de reorganização curricular, instrumento para articular conhecimentos e processo de integração das disciplinas. Também analisamos o tratamento teórico e a implementação da interdisciplinaridade segundo os PCNs. PCNs.Interdisciplinarity according to the PCNs Abstract The aim of this article is to analyze the meanings related to the concept of interdisciplinarity in the Parâmetros Curriculares Nacionais (PCNs) relative to Fundamental and High School Education. We used a method of conceptual analysis presented by Coombs and Daniels, which makes it possible to investigate a concept in a set of texts. The analysis indicated different meanings associated to the interdisciplinarity: epistemological approach, way to articulate contents, form of contribution of the disciplines, form of discipline organization in projects, perspective of curriculum reorganization; instrument for knowledge articulation and process of discipline integration. We also analyzed the theoretical treatment and implementation of interdisciplinarity according to the PCNs. Keywords: Education. Interdisciplinarity. Curriculum. PCNs.